Peningkatan Kemampuan Membaca Intensif Bagi Siswa SMAN 2 Rumbio Jaya - Raja Syamsidar; Alvi Puspita; TM Sum (Fakultas Ilmu Budaya Universitas Lancang Kuning, 2022)
The Science and Technology Program for the Community (IbM) that the team carried out was Improving the Intensive Reading Ability for Students of SMA N 2 Rumbio Jaya. The target to be achieved is to increase the intensive reading ability of the students of SMA N 2 Rumbio Jaya. As an additional value to be obtained, namely increasing the literary insight of the trainees because the reading material chosen by the team is the short story Helvy Tiana Rosa. The method used by the team to achieve this target is the lecture method, question and answer method and practice.